THE EDUCATION OF THE WEST: A FORMATIVE CHAPTER IN THE HISTORY OF CIVILIZATION (Author: R. Freeman Butts) - Magnusson, Roger (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1973)
R. Freeman Butts. THE EDUCATION OF THE WEST: A FORMATIVE CHAPTER IN THE HISTORY OF CIVILIZATION. New York: McGraw-Hill, 1973. 631 pp. 10.95.